Development and evaluation of a blog about cleft lip and cleft palate and hearing - Maximino, Luciana Paula; De Freitas Zambonato, Ticiana Cristina; Picolini-Pereira, Mirela Machado; De Castro Corrêa, Camila [UNESP]; Feniman, Mariza Ribeiro; Blasca, Wanderléia Quinhoneiro (Thieme, 2018)
Introduction Cleft lip and cleft palate can result in impairments in communication, specifically in hearing, making the use of technological resources such as blogs a fundamental guideline for health professionals. Objective The aim of this study was to prepare and analyze the access to a blog about cleft lip and cleft palate and hearing as a pedagogical tool for health professionals. Methods The first stage for the development of the blogwas the selection of the content that would be addressed and the respective illustrations. The second stage was making the blog available through theWordPress platform, and the third stage included the evaluation of the blog, of the access to theWordPress statistical features, and of the quality of the blog through the Emory questionnaire, which was answered by 75 professionals. Results The blog, titled Fissure and Hearing, was developed with the architecture of a digital information environment containing a system of organization, navigation, labeling and search (first stage). The address hosting the blog was: Http://fissuraeaudicao. wordpress.com (second stage). The result of the third stage included 56,269 views of the blog from different countries, and Brazil was the country with the highest viewing. Regarding the assessment by the Emory questionnaire, we found that for most of the major issues, the percentages obtained were or equal to 90%, while the analysis of the scales, navigation and structure presented the lowest scores. Conclusion The blog was developed and enabled greater access to information available on the web about cleft lip and cleft palate and hearing.
Keywords: Cleft lip; Cleft palate; Distance; Education; Health education; Hearing loss